Frontline Safety: Understanding the Workplace as a Site of Regulatory Engagement. (29th December 2016) - Almond, Paul; Gray, Garry C.
Abstract : The concept of frontline safety encapsulates an approach to occupational health and safety that emphasizes the "other side of the regulatory relationship"—the ways in which safety culture, individual responsibility, organizational citizenship, trust, and compliance are interpreted and experienced at the local level. By exploring theoretical tensions concerning the most appropriate way of conceptualizing and framing frontline regulatory engagement, we can better identify the ways in which conceptions of individuals (as rational, responsible, economic actors) are constructed and maintained through workplace interactions and decision making as part of the fulfillment of the ideological and constitutive needs of neoliberal labor markets.